Evapotranspiração de referência utilizando diferentes metodologias para o cálculo da radiação solar global, da temperatura e da umidade relativa do ar - Borges, Ronaldo Lima Moreira (2004)
The study was carried out in the experimental area of agribusiness Figood-Produção de Produtos Agrícolas Ltda. in the Distrito de Irrigação (irrigation district) Jaguaribe - Apodi (DIJA), Limoeiro do Norte, Ceará, Brazil, from July to December 2008 and consisted of two experiments. In the experiment I, the treatments consisted of five irrigation frequencies: F1 - total irrigation depth applied in the morning, F2– total irrigation depth applied in the afternoon, F3 -50% of the irrigation depth applied in the morning and 50% applied in the afternoon, F4-1/3 of the irrigation depth applied in the morning, 1/3 of the irrigation depth applied at noon, 1/3 of the irrigation depth applied in the afternoon; F5 -accumulated total irrigation depth applied every two days. In the experiment II, the treatments were five different doses of nitrogen fertilizer (50, 75, 100, 125 and 150% of the standard nitrogen fertilizer recommendation) applied by fertigation, defined based in the recommended farm's fertilizer amount (from soil analysis ). The experimental design (for both experiments) was organized in randomized blocks with five treatments and four replications. In both experiments, we evaluated the following variables: plant height, plant yield, stem diameter, branch length, number of fruits per plant, fruit diameter, and fruit weight. In the first experiment the average fruit weight ranged between 52.81 and 59.05 g. In experiment II, the average fruit weight ranged between 40.00 and 63.50 g. It was also observed a direct relationship between the number of fruits per plant and plant yield. The different irrigation frequencies did not statistically influence (p > 0.05) plant height, plant yield, stem diameter, branch length, number of fruits per plant, fruit diameter, and fruit weight in the period from 0 to 190 days after the first production pruning of the fig tree cv. Roxo Valinhos. The different levels of nitrogen fertigation applied in the period from 0 to 190 days after the first production pruning of the Roxo Valinhos fig tree did not statistically influence (p > 0.05) plant height, plant yield, stem diameter, branch length, number of fruits per plant, fruit diameter, and fruit weight.